EFFECTIVENESS OF ADOLESCENT REPRODUCTIVE HEALTH TRIAD EDUCATIONAL INTERVENTIONS IN IMPROVING ADOLESCENT REPRODUCTIVE HEALTH KNOWLEDGE AND ATTITUDES AT SMA NEGERI 1 KOTARIH - Anfrisa Gultom; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (RADJA PUBLIKA, 2026)
Adolescents are a vulnerable population due to limited knowledge of reproductive health, which increases the risk of unsafe sexual behavior, HIV/AIDS infection, and drug abuse. This study aimed to determine the effectiveness of the Triad Adolescent Reproductive Health (TRIAD KRR) educational intervention in improving adolescents’ knowledge and attitudes toward reproductive health. This study used a quantitative approach with a quasi-experimental one-group pretest–posttest design conducted at SMA Negeri 1 Kotarih, Serdang Bedagai Regency, North Sumatra. The sample consisted of 63 tenth-grade students selected using purposive sampling. Data were collected using validated questionnaires measuring knowledge and attitudes before and after the intervention. The intervention was delivered through interactive educational sessions covering sexuality, HIV/AIDS prevention, and drug abuse. Data analysis was performed using the Wilcoxon Signed Rank Test and effect size calculation. The results showed a significant increase in knowledge scores from 28.63 to 29.29 and attitude scores from 58.49 to 59.16 after the intervention (p < 0.05), with a large effect size, indicating the effectiveness of the TRIAD KRR education. This study concludes that TRIAD KRR educational intervention is effective in improving adolescents' knowledge and attitudes and can be used as a promotive and preventive strategy in school-based reproductive health programs.